0
$\begingroup$

Can anyone help me out on this boolean algebra simplification...im not sure with my answer.

X’YZ + XY’Z’ + X’Y’Z’ + XY’Z + XYZ my answer is x'yz+y'z'+xz but badly not sure of it! can you check thnks in advance

I am assuming the "()" with "'" means the over-score above the variables

$\endgroup$
0
$\begingroup$

\begin{align} XY'Z' + X'Y'Z' &= (X+X')Y'Z' \qquad &\mbox{distributivity}\\ &= Y'Z' \qquad &\mbox{ since } X' + X = 1\\ XY'Z + XYZ &= Y'XZ + YXZ \qquad &\mbox{commutativity}\\&= (Y'+Y)XZ \qquad &\mbox{distributivity}\\&= XZ \qquad &\mbox{ since }Y' + Y = 1\end{align}

So your answer is correct.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.